2022
DOI: 10.7759/cureus.21949
|View full text |Cite
|
Sign up to set email alerts
|

A 10-Year Tertiary Care Center Experience With Adrenalectomies for Adrenal Tumors

Abstract: BackgroundDue to limited data, our understanding of the trends and outcomes of adrenalectomy in the Saudi surgical practice is limited and insufficient. The aim of this study was to review the clinical data regarding the diagnosis and management of patients with adrenal masses and to assess the effect of surgeon specialty on the outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 17 publications
2
3
0
Order By: Relevance
“…Clinical and histopathological analyses of the resected tumors revealed that pheochromocytoma was the most common hormone-secreting tumor, followed by aldosterone-secreting tumors and steroid-secreting adrenal tumors. Other studies from developing countries yield similar results with an increased prevalence of catecholamine-secreting tumors [ 7 - 9 , 15 ]. Pheochromocytomas typically present with severe headaches and hypertension secondary to the catecholamine surge [ 4 ].…”
Section: Discussionsupporting
confidence: 70%
See 4 more Smart Citations
“…Clinical and histopathological analyses of the resected tumors revealed that pheochromocytoma was the most common hormone-secreting tumor, followed by aldosterone-secreting tumors and steroid-secreting adrenal tumors. Other studies from developing countries yield similar results with an increased prevalence of catecholamine-secreting tumors [ 7 - 9 , 15 ]. Pheochromocytomas typically present with severe headaches and hypertension secondary to the catecholamine surge [ 4 ].…”
Section: Discussionsupporting
confidence: 70%
“…Our study showed that 45.8% of the patients with adrenal mass were aged between 41 and 50 years, while the mean age of all study participants was 47.52 years. A similar study from Saudi Arabia on 55 patients showed similar results where the mean age of patients was 49.91 years [9]. Other studies also report similar findings where more than 35% of the patients were aged between 41 and 50 years [4,14].…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations